2001
DOI: 10.1034/j.1600-0420.2001.079004389.x
|View full text |Cite
|
Sign up to set email alerts
|

A previous abrasion in the contralateral eye influences the cell kinetics during healing of a central corneal abrasion

Abstract: ABSTRACT.Purpose: To study the influence of a previous erosion in the fellow eye on the proliferative response during healing of a central corneal erosion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Estil et al also showed that a previous corneal erosion in the fellow eye resulted in faster healing of the second eye, and explained that this corneal healing process was influenced by systemic factor(s). [ 10 ] Our data are consistent with those studies and further demonstrated that this systemic effect may influence the early phase of the fellow eye’s wound healing, which corresponds to the inflammatory phase. [ 20 ]…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Estil et al also showed that a previous corneal erosion in the fellow eye resulted in faster healing of the second eye, and explained that this corneal healing process was influenced by systemic factor(s). [ 10 ] Our data are consistent with those studies and further demonstrated that this systemic effect may influence the early phase of the fellow eye’s wound healing, which corresponds to the inflammatory phase. [ 20 ]…”
Section: Discussionsupporting
confidence: 92%
“…[ 9 ] Another study suggested that the corneal abrasion of the first eye affected the healing process of the corneal epithelium of the fellow eye by increasing cell proliferation. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the data indicate that the manipulation of one cornea with a contact lens affects the proliferation rate on the non-lens-wearing, contralateral cornea. Estil et al 39 have reported a similar cross talk reaction during wound healing. Inducing a wound in one cornea caused an increase in cell proliferation in the contralateral control cornea.…”
Section: Discussionmentioning
confidence: 77%
“…Fonn et al 28 found that the corneal thickness was significantly different between the control eyes of patients wearing unilaterally a high-oxygen-transmissible lens compared with the control eyes with the low-oxygen-transmissible lens. Furthermore, inducing a wound in one cornea resulted in an upregulation of proliferation in the contralateral control cornea, 29 and even tear film osmolality in the contralateral control eye can be affected after monocular soft lens wear. 30 Thus, corneal epithelial homeostasis in both eyes appears to be linked systemically through mechanism(s) that remain to be established.…”
Section: Discussionmentioning
confidence: 99%